Effect of private tutoring on university entrance examination performance in Turkey - Aysit Tansel; Fatma Bircan (Institute for the Study of Labor (IZA), 2005)
There is an excess demand for university education in Turkey. Highly competitive university entrance examination which rations the available places at university programs is very central to the lives of young people. In order to increase the chances of success of their children in the university entrance examination parents spend large sums of money on private tutoring (dersane) of their children. In this study, we investigate the factors that determine participation in private tutoring and the effect of private tutoring on getting placed at a university program. We further examine the impact of private tutoring on the scores of the applicants in the university entrance examination. The results indicate that controlling for other factors those students who receive private tutoring perform better in the university entrance examination.
Keywords: I2; J10; 330; private tutoring; university entrance examination achievement; Turkey